BUILDING TAX MORALE FOR SUSTAINABLE MICROENTERPRISE GROWTH: THE ROLE OF AWARENESS, FAIRNESS, AND TRUST - Jasrah Bahira D. Ibrahim (International Journal of Application on Economics and Business, 2025)
Achieving the United Nations Sustainable Development Goals (SDGs) depends not only on policy reforms but also on the fiscal behavior of citizens and entrepreneurs, making taxation a key driver of sustainable governance and inclusive development. Anchored in the Tax Morale Theory and Fiscal Exchange Theory, this study examines how tax awareness, perceived fairness, and trust in government relate to the tax morale of microbusiness owners in Marawi City, Philippines. Descriptive statistics indicated a high level of tax awareness but neutral perceptions of fairness, moderate trust in government, and tax morale. Correlation analysis showed that all three independent variables have a significant relationship with tax morale, with trust in government demonstrating the strongest relationship. Multiple regression analysis further revealed that trust in government was the only significant predictor of tax morale. These findings highlight that awareness and fairness contribute to tax morale primarily when accompanied by institutional trust. Strengthening transparency, equitable enforcement, and participatory fiscal management is therefore essential to foster voluntary compliance and promote the sustainability of microenterprises in post-conflict Marawi City. The study underscores institutional trust as a cornerstone of responsible taxation behavior, which is essential for sustaining microentrepreneurship and advancing inclusive and resilient local governance.